2020
DOI: 10.1007/s42452-020-2730-3
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of meteorological drought using exponential smoothing models: a study on Bankura District, West Bengal, India

Abstract: Water scarcity and drought management is the burning issue in India and hence needs serious attention of researchers to develop rigorous plan and management. Areas that belong to various plateaus, e.g., Chotanagpur plateau, Deccan plateau, etc., are mostly affected by drought in India. In the past decade, Bankura District of West Bengal, which belongs to northeast part of Chotanagpur plateau, faced severe drought several times. However, the assessment of drought scenario in this area is far from conclusive sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…RMSE represents how spread out the residuals are. The RMSE is represented as follows (Chai & Draxler, 2014;Raha & Gayen, 2020):…”
Section: Root Mean Squared Error (Rmse)mentioning
confidence: 99%
See 1 more Smart Citation
“…RMSE represents how spread out the residuals are. The RMSE is represented as follows (Chai & Draxler, 2014;Raha & Gayen, 2020):…”
Section: Root Mean Squared Error (Rmse)mentioning
confidence: 99%
“…There are various simulation models are already developed in the field of civil engineering. The ARIMA model, is indeed the most commonly used model (Raha & Gayen, 2020). Due to its' univariate design and linearity assumption, the model is unable to consider the geographical interrelationships exists in the time series model.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that the CANFIS model predicted the SPI better than the other models, and prediction results were different for different meteorological stations and proposed that the CANFIS model can build a reliable expert intelligent system for predicting meteorological drought at multi-time scales and decision-making for remedial measures to cope with meteorological drought and can help to maintain sustainable water resources management (Malik et al 2020). Also, Raha & Gayen (2020) in their study simulated the SPI using double exponential (DE) and Holt-Winter (HW) exponential smoothing models for several time steps (e.g. 3, 6, 12, 24 and 48 months) from 1979 to 2014 in meteorological drought for Bankura District.…”
Section: Water Smartmentioning
confidence: 99%
“…Suppose the current time is t, and the observed value of the corresponding clock error series is x 1 , x 2 , • • • , x t , then the ES1 value of the clock bias time series at this time is [35,36]…”
Section: Exponential Smoothing Prediction Modelmentioning
confidence: 99%